PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BUDIDAYA AYAM KAMPUNG UNGGUL BALITBANGTAN (KUB) DI DESA LINAMNUTU, KECAMATAN AMANUBAN SELATAN - Filphin Adolfin Amalo; Inggrid Trinidad Maha; Heny Nitbani; Meity Marviana Laut; Nemay Anggadewi Ndaong; Dede Rival Novian (Jurnal Media Tropika, 2022)
This community service aims to provide assistance to the community in Linamnutu Village, South Amanuban District regarding intensive and modern management of KUB chicken farms. The methods used in this community service include making cages, counseling, handing over DOC, feed and cage equipment, as well as community assistance and ongoing monitoring. The conclusions obtained are increasing community knowledge and skills about the advantages of KUB chicken farming, KUB chicken farming business opportunities, KUB chicken maintenance and health management, and partner groups having entrepreneurial capital in a sustainable manner.